Phase I study of adjuvant chemotherapy with nab‐paclitaxel and S‐1 for stage III Lauren's diffuse‐type gastric cancer after D2 resection (NORDICA study). (25th June 2022) - Cui, Yuehong; Yu, Yiyi; Yu, Shan; Li, Wei; Wang, Yan; Li, Qian; Liu, Tianshu
Abstract: Purpose: The prognosis of diffuse‐type gastric cancer (DGC) is poorer than that of intestinal type, but S‐1 is a potential treatment option in DGC. This study explored the maximal tolerated dose (MTD) and the recommended dose for phase II study (RP2D) of nab‐paclitaxel combined with S‐1 (AS regimen) as adjuvant chemotherapy in stage III DGC. Methods: Patients with stage III DGC were recruited into this phase I dose‐escalation study between July 2019 and June 2020 in Zhongshan Hospital. Nab‐paclitaxel and S‐1 (80–120 mg/day, d1‐14, q3w) were administrated for 6 cycles, and then 8 cycles of S‐1 monotherapy were applied. The patients received nab‐paclitaxel at 180, 220, or 260 mg/m 2 according to the 3 + 3 design based on dose‐limiting toxicity (DLT). The primary endpoint was RP2D. Secondary endpoints were the 1‐year disease‐free survival (DFS) rate and adverse events (AEs). Results: One case experienced DLT in 180‐mg/m 2 dose group, subsequently three additional subjects were enrolled. DLT was not observed in the 220‐ and 260‐mg/m 2 dose groups (both n = 3). Therefore, the MTD has not reached, and the RP2D of nab‐paclitaxel would be 260 mg/m 2 . Five participants showed progressive disease, with three and two participants in the 180‐ and 220‐mg/m 2 dose groups, respectively. The 6‐, 12‐, and 18‐month DFS rates were 100%, 63.6%, and 50.9%, respectively. The most frequently observed AEs were neutropenia (83.3%) and leukopenia (66.7%). Conclusion: The RP2D of nab‐paclitaxel as adjuvant chemotherapy in DGC was 260 mg/m 2 . The AS regimen had a tolerable AE profile in stage III DGC. Abstract : This phase I dose‐escalation study of adjuvant nab‐paclitaxel plus S‐1 (AS) recruited patients with stage III DGC. The RP2D of nab‐paclitaxel as adjuvant chemotherapy in DGC was 260 mg/m 2 . The AS regimen had a tolerable AE profile in stage III DGC.